Methane and Trichloroethylene Degradation by Methylosinus trichosporium OB3b Expressing Particulate Methane Monooxygenase - Lontoh, Sonny (American Society for Microbiology, 1998)
Whole-cell assays of methane and trichloroethylene (TCE) consumption have been performed on Methylosinus trichosporium OB3b expressing particulate methane monooxygenase (pMMO). From these assays it is apparent that varying the growth concentration of copper causes a change in the kinetics of methane and TCE degradation. For M. trichosporium OB3b, increasing the copper growth concentration from 2.5 to 20 μM caused the maximal degradation rate of methane (V(max)) to decrease from 300 to 82 nmol of methane/min/mg of protein. The methane concentration at half the maximal degradation rate (K(s)) also decreased from 62 to 8.3 μM. The pseudo-first-order rate constant for methane, V(max)/K(s), doubled from 4.9 × 10(−3) to 9.9 × 10(−3) liters/min/mg of protein, however, as the growth concentration of copper increased from 2.5 to 20 μM. TCE degradation by M. trichosporium OB3b was also examined with varying copper and formate concentrations. M. trichosporium OB3b grown with 2.5 μM copper was unable to degrade TCE in both the absence and presence of an exogenous source of reducing equivalents in the form of formate. Cells grown with 20 μM copper, however, were able to degrade TCE regardless of whether formate was provided. Without formate the V(max) for TCE was 2.5 nmol/min/mg of protein, while providing formate increased the V(max) to 4.1 nmol/min/mg of protein. The affinity for TCE also increased with increasing copper, as seen by a change in K(s) from 36 to 7.9 μM. V(max)/K(s) for TCE degradation by pMMO also increased from 6.9 × 10(−5) to 5.2 × 10(−4) liters/min/mg of protein with the addition of formate. From these whole-cell studies it is apparent that the amount of copper available is critical in determining the oxidation of substrates in methanotrophs that are expressing only pMMO.